Bibliometric analysis of spatio-temporal model using a general product-sum based on a hydrological distance - Bachrudin, Achmad; Ruchjana, Budi Nurani; Abdullah, Atje Setiawan; Budiarto, Rahmat (Frontiers in Applied Mathematics and Statistics, 2022)
In the last two decades, the number of model developments in the field of Geostatistics increased rapidly, especially in the Spatio-temporal models. Almost of these models are based on Euclidean distance, only a few which based on non-Euclidean distance. The purpose of this study is to analyze and visualize the types of literatures on stationary Spatio-temporal models that utilize General Product-sum and Hydrological distance through bibliometric analysis methods, by considering a set of bibliometric metrics, including productive and impact measures, methods analysis, and co-authorships analysis. Scientific research works related to Spatio-temporal models using the product-sum field that consider hydrological aspects, published between 2002 and 2022 are reviewed. Some of the most relevant research works in this field and some of the newest trends are collected during September 2022 from Google Scholar, Scopus and Dimensions databases. The literature search method is carried out in two steps. Firstly, literature sources were obtained from Google Scholar, Scopus and Dimensions. Secondly, meta-analysis is performed using Harzing's Publish or Perish and VOSviewer software program. Total of 488 articles related to Spatio-temporal product-sum, and 8 articles related to Spatio-temporal product-sum based on hydrologic distance are selected. The analysis result shows that the proposed topic “Spatio-temporal model using product-sum based on hydrologic distance” has a different significant attribute from the existing research works, i.e.: the hydrologic distance. Therefore, the proposed topic can be considered has a novelty.